Principal management in instilling Islamic character in Islamic Kindergarten - Farahdiba, Ririn; Ramzi, Muhajirin; Marzoan, Lalu (Nashir Al-Kutub Indonesia, 2025)
This study is to describe the role of the principal management in instilling islamic character in TK islamic integration of the Muslim Madani. This type of study is a qualitative study with a case study approach, the data-gathering techniqused in this study is observation, interview, and documentation. The information gathered came from the headmaster and the class teacher and the companion teacher. The data analysis techniq used in the research are several stages of data condense. 2) display, and 3) verification.The study result that the headmaster's management of the imprinting of islamic character had been designed and that implementation of implementation to instill the character of islami so that schools could achieve their purposes, to evaluate more effectively so that schools could know what to lack and what to improve.